The use of the Rotterdam Transition Profile: 10 years in review - Zhang-Jiang Sofía; Gorter Jan Willem (De Gruyter, 2018)
The aim of this literature review was to describe the use and utility of the Rotterdam Transition Profile (RTP), as we near the tenth year since its publication in 2008. It is a tool to summarize a youth's transition process to adulthood by classifying various domains of participation and health care into developmental stages. This review provided a comprehensive synthesis of available knowledge on the RTP by summarizing published and grey literature. Using search terms related to transition, social participation, and questionnaire, a systematic search was conducted for literature up to November 2017 in MEDLINE and Embase databases, and was supplemented with a hand-search using Google Scholar and a general internet search using Google Search. Inclusion criteria were specified to determine the papers selected for review, yielding fifty-five materials for detailed review. Combined analysis of published and grey literature identified nine papers that used some form of the RTP as a measure, 18 materials that cited the RTP or its domains but did not employ it as a measure, and twenty-eight materials that cited the original RTP development and validation paper for information not directly related to the RTP. The literature demonstrated that the RTP seems to be a useful tool to describe and monitor the transition process of adolescents and young adults, in both research and clinical settings. While it has been used with youth of 14-31 years of age across genders and health conditions, more evidence is needed to demonstrate its psychometric properties beyond construct validity in young adults with cerebral palsy.